2009
DOI: 10.1111/j.1471-4159.2009.05968.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural cells secrete a unique repertoire of proteins

Abstract: Proteins that are released from cells consist of those in the extracellular matrix, as well as extracellular signaling and adhesion molecules. The majority of these extracellular proteins are, however, unknown. To determine their identity, we have used a proteomics approach to define proteins released from neurons, astrocytes and neural precursor cells. Using two-dimensional gels and liquid chromatography/mass spectrometry technology, it is shown that while astrocytes release a relatively small number of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Samples were then subject to LDS-PAGE and silver-staining (Invitrogen). Individual lanes of the gel were cut into 10-15 slices and digested with trypsin prior to mass spectrometry analysis using ESI-MS/ MS as described Schubert et al 2009). Data were analyzed using the Mascot algorithm (Matrix Science).…”
Section: Bisulfite Sequencing/cobra Analysismentioning
confidence: 99%
“…Samples were then subject to LDS-PAGE and silver-staining (Invitrogen). Individual lanes of the gel were cut into 10-15 slices and digested with trypsin prior to mass spectrometry analysis using ESI-MS/ MS as described Schubert et al 2009). Data were analyzed using the Mascot algorithm (Matrix Science).…”
Section: Bisulfite Sequencing/cobra Analysismentioning
confidence: 99%
“…Conditioned media were obtained as previously described (Schubert et al, 2009) and desalted by means of ion-exchange sepharose columns (GE Healthcare, Piscataway, NJ, USA), frozen in dry ice, and lyophilized. Lyophilized proteins were resuspended in 0.5 ml of sample buffer [8 M urea, 4% (w/v) 3-[(3-Cholamidopropyl) dimethylammonio]-1-propanesulfonate, 40 mM Tris, 0.2% Bio-Lyte 3–10 ampholytes (Bio-Rad, Hercules, CA, USA), 50 mM dithiothreitol].…”
Section: Methodsmentioning
confidence: 99%
“…Gels were fixed in 50% methanol overnight and stained with silver. Gel spots from 2-D gels were excised and in-gel digested with trypsin and analyzed by LC electrospray ionization MS, as described previously (Schubert et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…The characterization of proteins released from neurons, astrocytes and neural precursor cells by 2DE and LC-MS has been recently reported [47,48]. These studies revealed that the secreted extracellular pool is specific for a given cell population, including proteins involved in cell-cell interactions, energy metabolism, redox regulations and several molecular chaperones.…”
Section: Neural Cells Secretomementioning
confidence: 97%
“…Curiously, several 'housekeeping' proteins (e.g. lactate dehydrogenase, creatine kinase, malate dehydrogenase, proteasome subunits, vimentin) were identified among the secreted proteins [48,49]. It has been hypothesized that this observation may reflect the selective release of a subset of internal cellular contents via exosomes, which contain a variety of cytoplasmic proteins that are deposited outside the cell [50].…”
Section: Neural Cells Secretomementioning
confidence: 97%